State Favoritism in Licensing Mining Services Business to Domestic Companies - Budiana Budiana (Rechtsnormen: Journal of Law, 2024)
Background. We often hear about the involvement of foreign companies/investments in the energy and mineral mining business, discussions about foreign investment are always a conversation and the spotlight of various parties. Purpose. the purpose of this study is to measure the extent of the benefits obtained if the exploitation / exploitation of natural resources, especially mineral natural resource mining, is left to foreign investors, what reasons underlie the state to open opportunities for foreign investment to manage the wealth of Indonesian mining, energy and mineral products. Method. This research is a normative legal research using two approaches, namely conceptual approach, and statute approach. Results. The state is entrusted by all Indonesian people through the 45 Constitution to control all natural resources and be used to the greatest extent for the prosperity of the people. Conclusion. The regulation of this mandate must of course be based on legislation as a foothold for implementing the law so that the direction of natural resource management does not deviate from the basic norm, which is controlled by the state and for the prosperity of the people.